Pembangunan Kakas Bantu Pengukuran Maintainability pada Tahap Perancangan Perangkat Lunak - Sigit Widodo; Fajar Pradana; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Maintainability is defined as the ease of modifying a system or component of software. Previously there were studies from Kumar and Dhanda in 2015 namely "Maintainability Measurement Model for Object Oriented Design" which states that the results of maintainability values ​​can be known based on flexibility and extendibility in the class diagram. The study explained that the calculation is quite time-consuming because it has to do the calculation process of the 4 metrics of Quality Model for Object-Oriented Design (QMOOD). Therefore this research is intended to build a tool for measuring maintainability at the stage of software design automatically by implementing the calculations found in the Kumar and Dhanda research. Development is done using the Waterfall method. The tools are desktop-based by entering the XML class diagram file in a standard simple format from the visual paradigm application to determine the value of maintainability. These tools have a time based efficiency of 0.67 tasks/second, which is faster than manual measurement which has a time based efficiency of 0.0082 tasks/second. Besides that, it has overall relative efficiency or the success of completing tasks by 100%.